An Overview of Physicochemical Properties and Engine Performance Using Rubber Seed Biodiesel”“Plastic Pyrolysis Oil Blends in Diesel Engines - Bisrul Hapis Tambunan; Himsar Ambarita; Tulus Burhanuddin Sitorus; Abdi Hanra Sebayang; Ahmad Masudie (Automotive Experiences, 2023)
Rubber Seed Biodiesel (RSB) and Plastic Pyrolysis Oil (PPO) deserve to be considered as alternative fuels for diesel engines, because of their advantages such as large raw material resources, derived from free or waste feedstock and the use of plastic waste as fuel can prevent environmental pollution. Due to their almost identical densities, RSB and PPO can be mixed homogeneously. In general, the use of a mixture of RSB and petroleum diesel in diesel engines shows positive performance, both engine performance and emissions, as well as the use of mixed PPO and diesel fuel. Although RSB has a good cetane number and flash point, on the other hand, RSB also has disadvantages in its physiochemical properties, such as low oxidation stability, high acid value, low heating value, and high viscosity. Likewise, PPO has good oxidation stability, acid value, and viscosity, but the flash point, CO, and HC emissions are also bad. This article tries to describe the opportunity to mix RSB and PPO, to find the best composition between RSB and PPO which shows the best fuel physiochemical properties and engine performance.